Efisiensi Persediaan Bahan Baku (Studi Kasus Temulawak di PT Jamu Air Mancur) - Clarisa Candra Utama; Erlyna Wida Riptanti; Agustono Agustono (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The primary challenge in raw material inventory management for manufacturing companies is determining accurate inventory estimates that are sufficient to support smooth production while minimizing excess inventory costs. The implementation of an efficient inventory management policy enables companies to minimize inventory costs. The purpose of this study is to improve the efficiency of inventory management of temulawak raw materials at PT Jamu Air Mancur. In this study, data analysis was carried out using the Economic Order Quantity (EOQ) method and Reorder Point analysis. Based on the findings obtained, it can be concluded that the optimal frequency of purchasing temulawak raw materials at PT Jamu Air Mancur, as determined by applying the EOQ method, is 7 times a year. The results show that the application of EOQ significantly optimises inventory management through the determination of the right reorder point and order quantity. This approach leads to more efficient stock control, as well as a decrease in overall inventory costs. These findings confirm the effectiveness of the EOQ method in supporting cost-efficient strategies and enhancing the company's operational performance.